2015
DOI: 10.1007/s10120-015-0480-5
|View full text |Cite
|
Sign up to set email alerts
|

The survival difference between gastric cancer patients from the UK and Japan remains after weighted propensity score analysis considering all background factors

Abstract: Background Previous studies comparing survival between gastric cancer (GC) patients from the West and the East were based on the assumption that background factors and prognostic factors were identical. The aim of the current study was to compare the survival of GC patients from the UK and Japan using weighted propensity score analysis after identifying all different background factors. Methods Data from 464 patients from the Leeds Teaching Hospital NHS Trust, Leeds, UK (LTHT), and 465 patients from the Kanaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Also, the generalizability of our results to the population outside the PS matched cohorts (ie those with dominant propensity for either LDG or ODG) is unwarranted. There might be disadvantageous conditions related to the incidence of complications in Western countries, such as patients with a higher body mass index and the greater proportion of patients who present at an advanced stage . The surgical outcomes of the present survey have been gradually established and refined since 1991, when Kitano et al first reported LDG in patients with GC in Japan.…”
Section: Discussionmentioning
confidence: 90%
“…Also, the generalizability of our results to the population outside the PS matched cohorts (ie those with dominant propensity for either LDG or ODG) is unwarranted. There might be disadvantageous conditions related to the incidence of complications in Western countries, such as patients with a higher body mass index and the greater proportion of patients who present at an advanced stage . The surgical outcomes of the present survey have been gradually established and refined since 1991, when Kitano et al first reported LDG in patients with GC in Japan.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, results with apatinib have been reported among Chinese patients. As a result of differences in the biologic background and treatment patterns between Eastern and Western patients with gastric cancer, 10 other studies should be awaited to confirm these data outside Asia.…”
Section: To the Editormentioning
confidence: 99%
“…The majority of gastric cancer patients are diagnosed at advanced stage, due to lacking early detecting methods31. To date, the outcomes for gastric cancer patients with similar TNM stage can be very different because of the heterogeneity of this tumor, and the prognostic models for gastric cancer patients are largely relied on the TNM stage5.…”
Section: Discussionmentioning
confidence: 99%